Curriculum Transformation of Religious Education in Central Sulawesi: Integration of Theological Disaster Literacy within Religious Teacher Certification Frameworks - Arman (AMUYA: JOURNAL OF MANAGEMENT, 2026)
Central Sulawesi, particularly the Palu-Koro Fault zone, faces high geological disaster risks. However, religious education in this region is not yet integrated with disaster mitigation needs. This is due to a curriculum dominated by metaphysical-eschatological aspects that tend to be fatalistic, and the absence of integrative modules in Religious Teacher Professional Development (PPG). This condition is exacerbated by low theology-based disaster literacy among educators, causing safety messages to be disconnected from religious narratives in the classroom. Objective: This study aims to formulate a curriculum transformation strategy for religious education by integrating theology-based disaster literacy into PPG modules. It seeks to provide a policy framework for standardizing religious teacher competencies in facing disaster risks in red zones. Methods: This research employs a qualitative approach using policy analysis methods based on William N. Dunn’s theory. Data collection techniques included PPG curriculum documentation studies, field observations in post-disaster madrasahs, and literature analysis of contextual theology and educational resilience. Policy alternative analysis was conducted through scoring criteria for effectiveness, efficiency, and responsiveness. Results: The findings indicate that integrating disaster literacy into PPG modules is the most effective "upstream" intervention to transform educators' habitus. This strategy reconstructs the cultural capital of religious teachers from fatalistic understandings toward "Active Tawakal," blending faith with mitigation science. The analysis suggests a formal mandate through a Decree of the Director General of Islamic Education to establish disaster literacy modules as a mandatory component for teacher certification in high-risk areas to ensure the sustainability of Disaster-Safe Education Units (SPAB). Keywords: Religious Curriculum; Disaster Literacy; Contextual Theology; PPG Module; Central Sulawesi; Educational Resilience.